Nilai-nilai moderasi beragama dalam pembelajaran sejarah peradaban islam - M. Al Qautsar Pratama (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
Religious moderation is one of the efforts of scientists in reaching the peak of the history of Islamic Civilization. The term various moderation refers to the 12 values that exist in Wasathiyah Islam. So when viewed from the description above, scientists in ancient times understood and also practiced the values that existed in Wasathiyah Islam such as tawasuth, tawazun, tasamuh, ishlah, musawah and so on. The attitude of religious moderation is indeed necessary when studying a lesson that contains religious values. Because basically a moderate attitude in religion is to accept all differences and groups and is not an extremist Islamic group and not a liberal who is more to the right and also more to the left but moderate in the midst of extremist Islam and Liberal Islam. Likewise, in terms of learning, especially learning the History of Islamic Civilization, a moderate attitude must also be practiced in such a way.